Implementasi Peraturan Bupati Mojokerto No. 66 Tahun 2021 Tentang Percepatan Penurunan Stunting Terintegritas Di Kecamatan Gondang - Cici Ariyanti; Dida Rahmadanik; M. Kendry Widiyanto (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
Stunting is a condition where toddlers fail to grow and develop due to malnutrition when they are in the womb until they are born into the world, but the condition of stunting is visible after the baby is 2 years old. Nutritional problems in toddlers, especially stunting experienced by toddlers, have the risk of hampering the growth and development of toddlers, especially if the stunting condition turns into stunting. The aim of this research is to determine and analyze the implementation of regulations to accelerate integrated stunting reduction as an effort to reduce stunting rates in Gondang sub-district. This type of research is qualitative research with descriptive methods. The research findings show that in implementing the Mojokerto Regent's regulatory policy No. 66 of 2021 concerning the acceleration of integrated stunting reduction, the district government has collaborated with the sub-district government, village government and the community effectively.